Silicon nanowire material and purification method and use thereof
Through the method of pickling, decentralization, and secondary pickling, the difficulty of chemical impurities and physical impurities in the silicon nano -normal lines in the silicon nanosaic wire is solved, and the high -purity silicon nano -wire purification is realized, and the electrochemical performance of lithium ion batteries is improved.
Patent Information
- Application Number
- CN202111582844.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-12-22
AI Technical Summary
The prior art is difficult to remove chemical and physical impurities in silicon nanowires simultaneously, resulting in a reduction in self-discharge and cycling performance of lithium-ion batteries.
Adopt the method of pickling, decentralized and secondary pickling, remove metal impurities by one pickling, and disperse silicon particles and thicker silicon threads twice. High purity is pure.
Effectively remove the chemical impurities and physical impurities in the silicon nano -wire, reduce the surface energy of the silicon nan navile, reduce the phenomenon of gathering, and improve the electrochemical performance of lithium -ion batteries.
Smart Images

Figure CN116332187B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon material purification, and in particular relates to a silicon nanowire material and a purification method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, high output voltage, green environmental protection and no memory effect, and have been widely used in various fields. Among them, silicon materials are considered to be highly promising negative electrode materials due to their excellent theoretical specific capacity, suitable voltage platform, abundant reserves in the earth's crust and environmental friendliness. However, as a semiconductor material, silicon has low electrical conductivity, and its volume changes greatly (320%) during charging and discharging, which produces internal stress and leads to problems such as pulverization of electrode materials.
[0003] At present, silicon nanowires are a typical representative of one-dimensional silicon nanomaterials. Unlike nanoparticle materials, the transmission of electrons does not have to overcome the interface barrier of a series of nanoparticle contacts, and the one-dimensional structure of silicon nanowires can also effectively buffer the volume effect. Therefore, silicon nanowire negative electrode materials have great potential application prospects. Commonly used silicon nanowire preparation methods, such as laser ablation, thermal evaporation, hydrothermal method, metal assisted chemical etching (MACE) or vapor deposition (CVD), all contain chemical impurities (metal impurities) and physical impurities (granular silicon and thick silicon wires). However, the current purification of silicon nanowires is still mainly focused on the removal of chemical impurities.
[0004] CN112607715A discloses a method for preparing high-purity α-phase silicon nitride nanowires, wherein the prepared silicon nitride nanowires are purified, and the purification method comprises immersing the silicon nitride nanowires in an acid for 5 to 30 minutes, then immersing them in an alkaline solution for 5 to 30 minutes, and finally washing and drying to obtain high-purity silicon nitride nanowires. This purification method can only remove chemical impurities in the silicon nitride nanowires, and cannot effectively remove physical impurities such as granular silicon nitride and silicon nitride wires with larger diameters.
[0005] CN101830447A discloses a method for preparing β-silicon nitride nanowires, wherein the prepared sample to be purified is purified, wherein the purification method comprises annealing the sample to be tested in air, washing it with a mixed solution of hydrofluoric acid and concentrated nitric acid, and then washing it with deionized water until the pH is neutral, thereby achieving the effect of removing carbon and silicon dioxide impurities. The purification method also does not consider the removal of physical impurities.
[0006] CN101804983A discloses a method for recovering, purifying and grading high-purity silicon carbide micropowder, the method comprising adding a flocculant to a silicon wafer cutting mortar to accelerate sedimentation, filtering to obtain solid matter; alkali washing, acid washing and cleaning the solid matter to obtain silicon carbide slurry; subsequently adding a dispersant to the silicon carbide slurry; finally, performing suspension hydraulic grading through a grading and semicolon device, controlling the grading and controlling the water flow to collect overflow micropowder, and drying to obtain high-purity silicon carbide products of different specifications and particle sizes. This method can purify silicon carbide particles of a certain particle size, but is not necessarily suitable for removing silicon particles from silicon nanowires.
[0007] Chemical impurities in silicon nanowires can cause serious self-discharge of batteries, while physical impurities in silicon nanowires can reduce the cycle performance of batteries. Therefore, designing a purification method for silicon nanowires that can simultaneously remove chemical and physical impurities is crucial to improving the electrochemical performance of batteries. Summary of the invention
[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a silicon nanowire material and a purification method and use thereof, which can simultaneously remove chemical impurities and physical impurities in the silicon nanowire material to be purified to obtain a purified silicon nanowire material, and can reduce the agglomeration phenomenon of the silicon nanowire material caused by its large specific surface energy.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for purifying a silicon nanowire material, the method comprising:
[0011] The silicon nanowire material to be purified is subjected to a first acid wash, a first dispersion, a second dispersion and a second acid wash in sequence to obtain a purified silicon nanowire material.
[0012] In the present invention, the first pickling is used to remove metal impurities; the first dispersion and the second dispersion are used to reduce the steric hindrance between silicon nanowires and remove silicon particles and thicker silicon wires; the second pickling is used to remove silicon dioxide impurities. Therefore, the chemical impurities and physical impurities in the silicon nanowire material to be purified are removed by two-step pickling and two-step dispersion to obtain high-purity silicon nanowires.
[0013] The silicon nanowire purification method provided by the present invention can simultaneously remove chemical impurities and physical impurities in the silicon nanowire material to be tested to obtain a high-purity silicon nanowire material, and can reduce the agglomeration phenomenon of the silicon nanowire material caused by the large specific surface energy.
[0014] As a preferred technical solution of the present invention, the primary dispersing process is carried out in a mixer.
[0015] Preferably, the mixer comprises a double planetary mixer.
[0016] In the present invention, the dispersion head of the double planetary mixer is sawtooth-shaped and is located at 2 / 3 of the liquid level of the first silicon nanowire slurry obtained by one acid wash to ensure the dispersion of the silicon nanowires, thereby promoting the separation of silicon particles and thicker silicon wires from the silicon nanowires.
[0017] Preferably, the rotation speed of the stirrer is 15 to 80 rpm, for example, it can be 15 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm or 80 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the speed of the disperser head of the stirrer is 500-3000 rpm, for example, it can be 500 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1500 rpm, 2000 rpm, 2200 rpm, 2500 rpm, 2800 rpm or 3000 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] The present invention limits the rotation speed of the dispersion head to 500-3000 rpm. When the rotation speed of the dispersion head is lower than 500 rpm, the aspect ratio of the silicon nanowires will be too large, making it difficult to disperse. The impurities in the silicon particles will not be easily separated, and coating will be difficult when applied to negative electrode materials for lithium-ion batteries. When the rotation speed of the dispersion head is higher than 3000 rpm, the aspect ratio of the silicon nanowires will be too small, forming a suspension together with the silicon particles, and the silicon particles cannot be effectively separated.
[0020] Preferably, the time for the primary dispersion is 3 to 90 min, for example, 3 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] As a preferred technical solution of the present invention, the secondary dispersion process is carried out under stirring.
[0022] In the present invention, the first silicon nanowire suspension is placed in a reactor for stirring, and under the action of a dispersant, the separation of silicon nanowires from silicon particles and thicker silicon wires in the first silicon nanowire suspension is further promoted. In the secondary dispersion process, silicon particles and thicker silicon wires gradually settle at the bottom of the reactor to form a precipitate, while the silicon nanowires are suspended in the solution to form a suspension.
[0023] Preferably, the stirring speed is 10 to 200 rpm, for example, it can be 10 rpm, 20 rpm, 40 rpm, 60 rpm, 80 rpm, 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm or 200 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] The present invention limits the stirring speed of secondary dispersion to 10-200 rpm. When the stirring speed is lower than 10 rpm, the disturbance force is small and the bond energy between the silicon nanowires and the silicon particles cannot be broken, thus making it difficult to separate the silicon nanowires from the silicon wires. When the stirring speed is higher than 200 rpm, the silicon particles will be stirred along with the silicon nanowires and cannot be precipitated by gravity.
[0025] Preferably, the stirring time is 3 to 90 min, for example, 3 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, a dispersant is added during the secondary dispersion process.
[0027] Preferably, based on the mass fraction of the silicon nanowire material to be purified as 100wt%, the added amount of the dispersant is 0.1-0.5wt%, for example, it can be 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] The present invention limits the amount of the dispersant added in the secondary dispersion to 0.1-0.5wt%. When the amount of the dispersant added is lower than 0.1wt%, the silicon nanowires cannot be well dispersed, thereby hindering the separation of silicon particles; when the amount of the dispersant added is higher than 0.5wt%, the silicon particles and the silicon nanowires form a suspension together, making it difficult to separate the silicon particles.
[0029] Preferably, the dispersant includes any one of ethanol, hexadecyltrimethylammonium bromide, sodium hexametaphosphate, triethylamine, polyvinyl pyrrolidone or polyethylene glycol, or a combination of at least two thereof.
[0030] The polyethylene glycol in the present invention includes polyethylene glycol with a molecular weight of 400 (PEG400) and polyethylene glycol with a molecular weight of 2000 (PEG2000).
[0031] Preferably, after the secondary dispersion, the suspension is filtered to obtain the first silicon nanowire material.
[0032] The present invention filters the secondary dispersed suspension to obtain a solid which is the first silicon nano material.
[0033] As a preferred technical solution of the present invention, the diameter of the silicon nanowires in the silicon nanowire material to be purified is 10 to 500 nm, for example, it can be 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the length of the silicon nanowires in the silicon nanowire material to be purified is 2 to 50 μm, for example, 2 μm, 5 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the chemical impurities in the silicon nanowire material to be purified include zinc and / or zinc chloride.
[0036] Preferably, based on the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of zinc is 0-30wt%, excluding 0, for example, it can be 1wt%, 5wt%, 15wt%, 20wt%, 25wt% or 30wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, based on the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of the zinc chloride is 0-40wt%, excluding 0, for example, it can be 1wt%, 5wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the physical impurities in the silicon nanowire material to be purified include silicon wires and / or silicon particles.
[0039] Preferably, the diameter of the silicon wire is 500nm to 400μm, for example, it can be 500nm, 1μm, 10μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm or 400μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, based on the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of the silicon wire is 0-40wt%, for example, it can be 0wt%, 5wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the particle size of the silicon particles is 500nm to 400μm, for example, it can be 500nm, 1μm, 10μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm or 400μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, based on the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of the silicon particles is 0-40wt%, and is not 0, for example, it can be 1wt%, 5wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] As a preferred technical solution of the present invention, the time for the single pickling is 1 to 5 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the primary acid solution used in the primary pickling includes any one of hydrochloric acid solution, nitric acid solution or sulfuric acid solution, or a combination of at least two of them.
[0045] Preferably, the concentration of the hydrochloric acid solution is 5 to 36 wt%, for example, it can be 5 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt% or 36 wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the concentration of the nitric acid solution is 5 to 42 wt%, for example, it can be 5wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or 42wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the concentration of the sulfuric acid solution is 5 to 98 wt%, for example, it can be 5 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt% or 98 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the mass ratio of the primary acid solution to the silicon nanowire material to be purified is (17-27):1, for example, 17:1, 19:1, 21:1, 23:1, 25:1 or 27:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In the present invention, when the primary acid solution is a hydrochloric acid solution, the mass ratio of the hydrochloric acid solution to the silicon nanowires to be purified is preferably 17:1; when the primary acid solution is a sulfuric acid solution, the mass ratio of the sulfuric acid solution to the silicon nanowires to be purified is preferably 27:1; when the primary acid solution is a nitric acid solution, the mass ratio of the nitric acid solution to the silicon nanowires to be purified is preferably 20:1.
[0050] Preferably, the first acid washing is followed by water washing to obtain a first silicon nanowire slurry.
[0051] Preferably, the pH value of the first silicon nanowire slurry is 6-8, for example, 6, 6.5, 7, 7.5 or 8, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0052] In the present invention, after the first acid wash, deionized water is used for washing until the pH value of the solution is 6 to 8, thereby obtaining a first silicon nanowire slurry.
[0053] As a preferred technical solution of the present invention, the time for the secondary pickling is 1 to 5 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the secondary acid solution used in the secondary pickling comprises a hydrofluoric acid solution.
[0055] Preferably, the concentration of the secondary acid solution is 5-40wt%, for example, 5wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the mass ratio of the secondary acid solution to the first silicon nanowire material is (10-20):1, for example, it can be 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the secondary acid washing is followed by water washing to obtain a second silicon nanowire slurry.
[0058] Preferably, the pH value of the second silicon nanowire slurry is 6-8, for example, 6, 6.5, 7, 7.5 or 8, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0059] In the present invention, after the secondary acid washing, deionized water is used for washing until the pH value of the solution is 6 to 8, thereby obtaining a second silicon nanowire slurry.
[0060] As a preferred technical solution of the present invention, the purification method also includes ultrasonic dispersion.
[0061] Preferably, the ultrasonic dispersion process comprises:
[0062] After adding the dispersant into the second silicon nanowire slurry, ultrasonic dispersion and filtration are performed in sequence to obtain a second silicon nanowire material.
[0063] Preferably, based on the mass fraction of the silicon nanowire material to be purified as 100wt%, the amount of dispersant added during the ultrasonic dispersion process is 0.1-0.5wt%, for example, it can be 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] Preferably, the ultrasonic dispersion time is 1 to 60 min, for example, 1 min, 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] Preferably, the frequency of the ultrasonic dispersion is 40-60 KHz, for example, 40 KHz, 42 KHz, 45 KHz, 48 KHz, 50 KHz, 52 KHz, 55 KHz, 58 KHz or 60 KHz, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0066] Preferably, the second silicon nanowire material is dried to obtain the purified silicon nanowire material.
[0067] Preferably, the temperature of the drying treatment is 60-110°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] Preferably, the drying treatment time is 5 to 30 hours, for example, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours or 30 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] As a preferred technical solution of the present invention, the purification method comprises:
[0070] (1) placing the silicon nanowire material to be purified in a primary acid solution for a primary acid wash for 1 to 5 hours, wherein the mass ratio of the primary acid solution to the silicon nanowire material to be purified is (17 to 27):1, and then washing with water to obtain a first silicon nanowire slurry with a pH of 6 to 8;
[0071] (2) placing the first silicon nanowire slurry obtained in step (1) in a stirrer with a rotation speed of 15 to 80 rpm and a dispersion head speed of 500 to 3000 rpm for a primary dispersion of 3 to 90 min to obtain a silicon nanowire suspension;
[0072] (3) adding a dispersant to the silicon nanowire suspension obtained in step (2), and performing secondary dispersion for 3 to 90 minutes at a stirring rate of 10 to 200 rpm, wherein the amount of the dispersant added is 0.1 to 0.5 wt % based on the mass fraction of the silicon nanowire material to be purified being 100 wt %, and then filtering the suspension to obtain a first silicon nanowire material;
[0073] (4) placing the first silicon nanowire material obtained in step (3) in a secondary acid solution with a concentration of 5 to 40 wt% for secondary acid washing for 1 to 5 h, wherein the mass ratio of the secondary acid solution to the first silicon nanowire material is (10 to 20):1, and then washing with water to obtain a second silicon nanowire slurry with a pH of 6 to 8;
[0074] (5) After adding a dispersant to the second silicon nanowire slurry obtained in step (4), ultrasonic dispersion is performed at a frequency of 40 to 60 Hz for 1 to 60 min, and the amount of the dispersant added is 0.1 to 0.5 wt % based on the mass fraction of the silicon nanowire material to be purified as 100 wt %. After filtering, the second silicon nanowire material is obtained, and then the second silicon nanowire material is dried at a temperature of 60 to 110° C. for 5 to 30 h to obtain a purified silicon nanowire material.
[0075] In a second aspect, the present invention provides a silicon nanowire material, which is obtained by the purification method described in the first aspect.
[0076] In a third aspect, the present invention provides a use of the silicon nanowire material described in the second aspect, wherein the silicon nanowire material is used as a negative electrode material for a lithium-ion battery.
[0077] The purified silicon nanowires provided by the present invention are used as the negative electrode material of the lithium ion battery, which effectively alleviates the battery self-discharge phenomenon caused by chemical impurities such as metals, and also alleviates the volume expansion phenomenon caused by physical impurities such as silicon particles and thicker silicon wires during the battery charge and discharge process, thereby avoiding the reduction of the cycle performance of the lithium ion battery.
[0078] Compared with the prior art, the present invention has the following beneficial effects:
[0079] The silicon nanowire material purification method provided by the present invention can simultaneously remove chemical impurities and physical impurities in the silicon nanowire material to be tested to obtain purified silicon nanowire material, and can reduce the agglomeration phenomenon caused by the large specific surface energy of the silicon nanowire material. In addition, using the purified silicon nanowire material provided by the present invention as the negative electrode material of the lithium ion battery can effectively alleviate the volume expansion phenomenon during the self-discharge and charge and discharge process of the lithium ion battery, and improve the electrochemical performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 This is a process flow chart of the silicon nanowire purification method provided in Examples 1-3 of the present invention.
[0081] Figure 2 This is a scanning electron microscope image of the silicon nanowire material to be purified provided in Example 1 of the present invention.
[0082] Figure 3 This is a scanning electron microscope image of the silicon nanowire material to be purified provided in Example 1 of the present invention.
[0083] Figure 4 This is the XRD diagram of the silicon nanowire material to be purified provided in Example 1 of the present invention.
[0084] Figure 5 This is a scanning electron microscope image of the purified silicon nanowire material provided in Example 1 of the present invention.
[0085] Figure 6 This is the XRD pattern of the purified silicon nanowire material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0086] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0087] Example 1
[0088] This embodiment provides a method for purifying silicon nanowires. Figure 1 As shown, the purification method comprises:
[0089] (1) placing the silicon nanowire material to be purified in a 20 wt % hydrochloric acid solution for a 3 h acid wash, wherein the mass ratio of the hydrochloric acid solution to the silicon nanowire material to be purified is 17:1, and then washing with deionized water to obtain a first silicon nanowire slurry with a pH of 7;
[0090] (2) placing the first silicon nanowire slurry obtained in step (1) in a double planetary mixer with a rotation speed of 50 rpm and a dispersion head speed of 2000 rpm for 50 min to obtain a first silicon nanowire suspension;
[0091] (3) adding ethanol to the first silicon nanowire suspension obtained in step (2), and performing secondary dispersion for 50 min at a stirring rate of 100 rpm, wherein the amount of ethanol added is 0.3 wt % based on the mass fraction of the silicon nanowire material to be purified being 100 wt %, and then filtering the suspension to obtain the first silicon nanowire material;
[0092] (4) placing the first silicon nanowire material obtained in step (3) in a 25 wt % hydrofluoric acid solution for secondary pickling for 3 h, wherein the mass ratio of the hydrofluoric acid solution to the first silicon nanowire material is 15:1, and then washing with deionized water to obtain a second silicon nanowire slurry with a pH of 7;
[0093] (5) After adding ethanol to the second silicon nanowire slurry obtained in step (4), ultrasonic dispersion is performed at a frequency of 50 kHz for 30 minutes. Based on the mass fraction of the silicon nanowire material to be purified as 100 wt%, the amount of ethanol added is 0.3 wt%. After filtration, the second silicon nanowire material is obtained. Subsequently, the second silicon nanowire material is dried at a temperature of 80° C. for 20 hours to obtain a purified silicon nanowire material.
[0094] The scanning electron microscope image of the silicon nanowire material to be purified in this embodiment is as follows Figure 2 and Figure 3 As shown, the XRD pattern is Figure 4 As shown; the scanning electron microscope image of the purified silicon nanowire material obtained in this example is as shown Figure 5 As shown, the XRD pattern is Figure 6 shown.
[0095] Example 2
[0096] This embodiment provides a method for purifying silicon nanowires. Figure 1 As shown, the purification method comprises:
[0097] (1) placing the silicon nanowire material to be purified in a 25 wt % nitric acid solution for a 5 h acid wash, wherein the mass ratio of the nitric acid solution to the silicon nanowire material to be purified is 20:1, and then washing with deionized water to obtain a first silicon nanowire slurry with a pH of 8;
[0098] (2) placing the first silicon nanowire slurry obtained in step (1) in a double planetary mixer with a rotation speed of 15 rpm and a dispersion head speed of 500 rpm for 90 min to obtain a first silicon nanowire suspension;
[0099] (3) adding cetyltrimethylammonium bromide to the first silicon nanowire suspension obtained in step (2), and performing secondary dispersion for 3 min at a stirring rate of 200 rpm, wherein the amount of cetyltrimethylammonium bromide added is 0.5 wt % based on the mass fraction of the silicon nanowire material to be purified being 100 wt %, and then filtering the suspension to obtain the first silicon nanowire material;
[0100] (4) placing the first silicon nanowire material obtained in step (3) in a 40 wt % hydrofluoric acid solution for secondary pickling for 1 h, wherein the mass ratio of the hydrofluoric acid solution to the first silicon nanowire material is 10:1, and then washing with deionized water to obtain a second silicon nanowire slurry with a pH of 8;
[0101] (5) After adding cetyltrimethylammonium bromide to the second silicon nanowire slurry obtained in step (4), ultrasonic dispersion is performed at a frequency of 60 kHz for 1 min. Based on the mass fraction of the silicon nanowire material to be purified as 100 wt%, the amount of cetyltrimethylammonium bromide added is 0.5 wt%. After filtration, the second silicon nanowire material is obtained. Subsequently, the second silicon nanowire material is dried at a temperature of 110° C. for 5 h to obtain a purified silicon nanowire material.
[0102] Example 3
[0103] This embodiment provides a method for purifying silicon nanowires. Figure 1 As shown, the purification method comprises:
[0104] (1) placing the silicon nanowire material to be purified in a 50 wt % sulfuric acid solution for an acid wash for 1 h, wherein the mass ratio of the sulfuric acid solution to the silicon nanowire material to be purified is 27:1, and then washing with deionized water to obtain a first silicon nanowire slurry with a pH of 6;
[0105] (2) placing the first silicon nanowire slurry obtained in step (1) in a double planetary mixer with a rotation speed of 80 rpm and a dispersion head speed of 3000 rpm for 3 min to obtain a first silicon nanowire suspension;
[0106] (3) adding polyvinyl pyrrolidone to the first silicon nanowire suspension obtained in step (2), and performing secondary dispersion for 90 minutes at a stirring rate of 10 rpm, wherein the amount of polyvinyl pyrrolidone added is 0.1 wt % based on the mass fraction of the silicon nanowire material to be purified being 100 wt %, and then filtering the suspension to obtain the first silicon nanowire material;
[0107] (4) placing the first silicon nanowire material obtained in step (3) in a 5 wt % hydrofluoric acid solution for secondary pickling for 5 h, wherein the mass ratio of the hydrofluoric acid solution to the first silicon nanowire material is 20:1, and then washing with deionized water to obtain a second silicon nanowire slurry with a pH of 6;
[0108] (5) After adding triethylamine to the second silicon nanowire slurry obtained in step (4), ultrasonic dispersion is performed at a frequency of 40 kHz for 60 minutes, and the amount of triethylamine added is 0.1 wt% based on the mass fraction of the silicon nanowire material to be purified as 100 wt%. The second silicon nanowire material is obtained after filtration, and then the second silicon nanowire material is dried at a temperature of 60° C. for 30 hours to obtain a purified silicon nanowire material.
[0109] Example 4
[0110] The difference between this embodiment and embodiment 1 is that the speed of the dispersing head in step (2) is 400 rpm, and the other process parameters and operation steps are the same as those in embodiment 1.
[0111] Example 5
[0112] The difference between this embodiment and embodiment 1 is that the speed of the dispersing head in step (2) is 3200 rpm, and the other process parameters and operation steps are the same as those in embodiment 1.
[0113] Example 6
[0114] The difference between this embodiment and embodiment 1 is that the stirring rate in step (3) is 5 rpm, and the other process parameters and operation steps are the same as those in embodiment 1.
[0115] Example 7
[0116] The difference between this embodiment and embodiment 1 is that the stirring rate in step (3) is 220 rpm, and the other process parameters and operation steps are the same as those in embodiment 1.
[0117] Example 8
[0118] The difference between this embodiment and embodiment 1 is that the amount of ethanol added in step (3) is 0.05 wt %, and the other process parameters and operation steps are the same as those in embodiment 1.
[0119] Example 9
[0120] The difference between this embodiment and embodiment 1 is that the amount of ethanol added in step (3) is 0.7 wt %, and the other process parameters and operation steps are the same as those in embodiment 1.
[0121] Example 10
[0122] The difference between this embodiment and embodiment 1 is that the concentration of the hydrochloric acid solution in step (1) is 3 wt %, and the other process parameters and operation steps are the same as those in embodiment 1.
[0123] Embodiment 11
[0124] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the hydrochloric acid solution to the silicon nanowire material to be purified is 13:1, and the other process parameters and operation steps are the same as those in embodiment 1.
[0125] Example 12
[0126] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the hydrochloric acid solution to the silicon nanowire material to be purified is 30:1, and the other process parameters and operation steps are the same as those in embodiment 1.
[0127] Comparative Example 1
[0128] The difference between this comparative example and Example 1 is that step (2) and step (3) are omitted, that is, the primary dispersion and the secondary dispersion are omitted, and the remaining process parameters and operating steps are the same as those in Example 1.
[0129] Comparative Example 2
[0130] The difference between this comparative example and Example 1 is that step (2) is omitted, that is, one dispersion is omitted, and the remaining process parameters and operating steps are the same as those in Example 1.
[0131] Comparative Example 3
[0132] The difference between this comparative example and Example 1 is that step (3), that is, the secondary dispersion, is omitted, and the remaining process parameters and operating steps are the same as those of Example 1.
[0133] Comparative Example 4
[0134] The difference between this comparative example and Example 1 is that step (1) is omitted, that is, one pickling is omitted, and the remaining process parameters and operating steps are the same as those in Example 1.
[0135] The test results of the chemical impurity element (Zn) content in the silicon nanowire materials to be purified and the purified silicon nanowire materials in Examples 1-12 and Comparative Examples 1-4 are shown in Table 1.
[0136] Table 1
[0137]
[0138]
[0139] The purified silicon nanowire materials of Examples 1-12 and Comparative Examples 1-4 were used as negative electrode materials to conduct electrochemical performance tests:
[0140] (1) Preparation of negative electrode sheet: Silicon nanowires, conductive agent (conductive carbon black SP), and binder (polyacrylic acid) were mixed in a weight ratio of 8:1:1 with a solid content of 100%. The above mixture was adjusted into a slurry with deionized water and evenly coated on the copper foil with a wet thickness of 150 μm. After air drying, it was rolled to 50 μm and dried in a vacuum oven at 110°C for 20 hours to obtain an electrode sheet with a diameter of 12 mm.
[0141] (2) Battery assembly: The counter electrode is a metallic lithium electrode, the separator is Celgard 2400, and the electrolyte is 1 mol / L LiPF 6 / EC+DEC were assembled into CR2032 button half-cells in a glove box filled with argon atmosphere.
[0142] (3) Self-discharge performance test parameters: The first cycle charging capacity is recorded as C1. After discharging at 25°C and leaving for 24 hours, charging is performed again. The second cycle charging capacity is recorded as C2. (1-C2 / C1)×100% is used to represent the 24-hour self-discharge rate.
[0143] (4) Cycle performance test parameters: A Xinwei 5V / 50mA battery tester was used to perform 100 charge and discharge cycles at a rate of 0.1C. The first cycle charge capacity was recorded as C1, the 100th cycle charge capacity was recorded as C100, and C100 / C1×100% was the 100-cycle capacity retention rate.
[0144] The performance test results of lithium ion batteries prepared by using the purified silicon nanowire materials of Examples 1-12 and Comparative Examples 1-4 as negative electrode materials are shown in Table 2.
[0145] Table 2
[0146]
[0147]
[0148] From Table 1 and Table 2, we can get:
[0149] (1) The zinc content in the purified silicon nanowire materials in Examples 1-3 is significantly reduced, and when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the volume expansion phenomenon during the self-discharge and charge-discharge processes of the lithium-ion batteries can be effectively alleviated, thereby improving the electrochemical performance of the lithium-ion batteries. This indicates that the silicon nanowire purification method provided by the present invention can simultaneously achieve the effect of effectively removing chemical impurities and physical impurities in the silicon nanowires to be tested, and reduce the agglomeration phenomenon of the silicon nanowire materials caused by the large specific surface energy.
[0150] In addition, the silicon nanowires to be tested in Example 1 were characterized by scanning electron microscopy and XRD. Figure 2 , Figure 3 and Figure 4 As shown in the figure, it can be seen that the silicon nanowires to be tested are doped with a large number of silicon particles and relatively thick silicon wires, and the diffraction peaks of zinc and zinc chloride can be clearly seen in the XRD graph, indicating that zinc and zinc chloride chemical impurities exist in the silicon nanowires to be tested. The silicon nanowires purified in Example 1 were characterized by scanning electron microscopy and XRD, as shown in FIG. Figure 5 and Figure 6 As shown in the figure, it can be seen that the content of silicon particles and thicker silicon wires in the purified silicon nanowires is significantly reduced, and it can be seen from the XRD diagram of the purified silicon nanowires that the diffraction peaks of zinc and zinc chloride disappear, which can also be explained that the silicon nanowire purification method provided by the present invention can effectively remove chemical impurities and physical impurities in the silicon nanowires to be tested at the same time.
[0151] (2) The zinc content in the purified silicon nanowire materials in Examples 4 and 5 is similar to that in Example 1, and when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the self-discharge rate of the lithium-ion batteries is also similar to that in Example 1, but the cycle performance of the lithium-ion batteries is lower than that in Example 1, indicating that the purified silicon nanowire materials provided in Examples 4 and 5 cannot effectively remove the physical impurities in the silicon nanowires to be tested, and thus cannot alleviate the volume expansion during the battery charging and discharging process. This is because the speed of the dispersing head in the primary dispersing process in Example 4 is too low, while the speed of the dispersing head in the primary dispersing process in Example 5 is too high. When the speed of the dispersing head is too low, the aspect ratio of the silicon nanowires will be too large, making it difficult to disperse, and the impurities in the silicon particles will not be easily separated, and it will be difficult to coat when applied to the negative electrode materials for lithium-ion batteries; when the speed of the dispersing head is too high, the aspect ratio of the silicon nanowires will be too small, forming a suspension together with the silicon particles, and the silicon particles cannot be effectively separated.
[0152] (3) The zinc content in the purified silicon nanowire materials in Examples 6 and 7 is similar to that in Example 1, and when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the self-discharge rate of the lithium-ion batteries is also similar to that in Example 1, but the cycle performance of the lithium-ion batteries is lower than that in Example 1, indicating that the purified silicon nanowire materials provided in Examples 6 and 7 are also unable to effectively remove physical impurities in the silicon nanowires to be tested, thereby unable to alleviate the volume expansion during the battery charging and discharging process. This is because the stirring speed of the secondary dispersion in Example 6 is too low, while the stirring speed of the secondary dispersion in Example 7 is too high. When the stirring speed is too low, the disturbance force is small, and the bond energy between the silicon nanowires and the silicon particles cannot be broken, making it difficult to separate from the silicon wires; when the stirring speed is too high, the silicon particles are stirred together with the silicon nanowires and cannot be precipitated by gravity.
[0153] (4) The zinc content in the purified silicon nanowire materials in Examples 8 and 9 is similar to that in Example 1, and when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the self-discharge rate of the lithium-ion batteries is also similar to that in Example 1, but the cycle performance of the lithium-ion batteries is lower than that in Example 1, indicating that the purified silicon nanowire materials provided in Examples 8 and 9 are also unable to effectively remove physical impurities in the silicon nanowires to be tested, thereby unable to alleviate the volume expansion during the battery charging and discharging process. This is because the amount of dispersant added in the secondary dispersion process in Example 8 is too low, while the amount of dispersant added in the secondary dispersion process in Example 9 is too high. When the amount of dispersant added is too low, the silicon nanowires cannot be well dispersed, thereby hindering the separation of silicon particles; when the amount of dispersant added is too high, the silicon particles and the silicon nanowires form a suspension together, thereby making it difficult to separate the silicon particles.
[0154] (5) The zinc content in the purified silicon nanowire materials in Examples 10 and 11 is higher than that in Example 1, and when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the electrochemical performance of the lithium-ion batteries is lower than that in Example 1. This is because the concentration of hydrochloric acid in the first pickling in Example 10 is too low, and the amount of hydrochloric acid added in the first pickling in Example 11 is too low. The zinc content in the purified silicon nanowire materials in Example 12 is similar to that in Example 1, and when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the self-discharge rate of the lithium-ion batteries is also similar to that in Example 1, but the cycle performance of the lithium-ion batteries is lower than that in Example 1. This is because the amount of hydrochloric acid added in Example 12 is too high. This shows that the appropriate concentration and amount of hydrochloric acid are crucial to removing chemical impurities in the silicon nanowires to be tested.
[0155] (6) The zinc content in the purified silicon nanowire materials in Comparative Examples 1-3 is similar to that in Example 1, but when the purified silicon nanowire materials are used as negative electrode materials for lithium-ion batteries, the electrochemical performance of the lithium-ion batteries is much lower than that of Example 1. The zinc content in the purified silicon nanowire materials in Comparative Example 4 is much higher than that in Example 1, and the electrochemical performance of the lithium-ion battery is also much lower than that of Example 1. This shows that under the interaction of the first pickling, the first dispersion and the second pickling, the physical impurities and chemical impurities in the silicon nanowire materials to be tested can be effectively removed at the same time, thereby effectively alleviating the self-discharge of the lithium-ion battery and the volume expansion phenomenon during the charge and discharge process, and further improving the electrochemical performance of the lithium-ion battery.
[0156] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for purifying silicon nanowire material, characterized in that: The purification method comprises: The silicon nanowire material to be purified is subjected to a first acid wash, a first dispersion, a second dispersion and a second acid wash in sequence to obtain a purified silicon nanowire material; The primary dispersion process is carried out in a mixer; the speed of the dispersion head of the mixer is 500 to 3000 rpm; The secondary dispersion process is carried out in a reactor, and a dispersant is added during the secondary dispersion process; The secondary dispersion process is carried out under stirring; the stirring speed is 10 to 200 rpm; The diameter of the silicon nanowires in the silicon nanowire material to be purified is 10 to 500 nm; the length of the silicon nanowires in the silicon nanowire material to be purified is 2 to 50 μm; the chemical impurities in the silicon nanowire material to be purified include zinc and / or zinc chloride; the physical impurities in the silicon nanowire material to be purified include silicon wires and / or silicon particles.
2. The purification method according to claim 1, characterized in that The mixer comprises a double planetary mixer.
3. The purification method according to claim 1, characterized in that The rotating speed of the stirrer is 15-80 rpm.
4. The purification method according to claim 1, characterized in that The time of the primary dispersion is 3 to 90 minutes.
5. The purification method according to claim 1, characterized in that: The stirring time is 3 to 90 minutes.
6. The purification method according to claim 1, characterized in that: Based on the mass fraction of the silicon nanowire material to be purified being 100wt%, the added amount of the dispersant is 0.1-0.5wt%.
7. The purification method according to claim 1, characterized in that: The dispersant includes any one of ethanol, hexadecyltrimethylammonium bromide, sodium hexametaphosphate, triethylamine, polyvinyl pyrrolidone or polyethylene glycol, or a combination of at least two thereof.
8. The purification method according to claim 1, characterized in that: After the secondary dispersion, the suspension is filtered to obtain the first silicon nanowire material.
9. The purification method according to claim 1, characterized in that: Based on the mass fraction of the silicon nanowire material to be purified being 100wt%, the mass fraction of zinc is 0-30wt%, excluding 0.
10. The purification method according to claim 1, characterized in that: Taking the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of the zinc chloride is 0-40wt%, excluding 0.
11. The purification method according to claim 1, characterized in that: The diameter of the silicon wire is 500nm-400μm.
12. The purification method according to claim 1, characterized in that: Taking the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of the silicon wire is 0-40wt%.
13. The purification method according to claim 1, characterized in that: The particle size of the silicon particles is 500nm-400μm.
14. The purification method according to claim 1, characterized in that: Taking the mass fraction of the silicon nanowire material to be purified as 100wt%, the mass fraction of the silicon particles is 0-40wt% and is not 0.
15. The purification method according to claim 1, characterized in that: The time of the first pickling is 1 to 5 hours.
16. The purification method according to claim 1, characterized in that: The primary acid solution used in the primary pickling includes any one of hydrochloric acid solution, nitric acid solution or sulfuric acid solution, or a combination of at least two of them.
17. The purification method according to claim 16, characterized in that: The concentration of the hydrochloric acid solution is 5-36 wt %.
18. The purification method according to claim 16, characterized in that: The concentration of the nitric acid solution is 5-42 wt %.
19. The purification method according to claim 16, characterized in that: The concentration of the sulfuric acid solution is 5-98 wt %.
20. The purification method according to claim 16, characterized in that: The mass ratio of the primary acid solution to the silicon nanowire material to be purified is (17-27):
1.
21. The purification method according to claim 1, characterized in that: The first acid washing is followed by water washing to obtain a first silicon nanowire slurry.
22. The purification method according to claim 21, characterized in that The pH of the first silicon nanowire slurry is 6-8.
23. The purification method according to claim 1, characterized in that: The secondary pickling time is 1 to 5 hours.
24. The purification method according to claim 8, characterized in that: The secondary acid solution used in the secondary pickling includes a hydrofluoric acid solution.
25. The purification method according to claim 24, characterized in that The concentration of the secondary acid solution is 5-40 wt %.
26. The purification method according to claim 24, characterized in that The mass ratio of the secondary acid solution to the first silicon nanowire material is (10-20):
1.
27. The purification method according to claim 1, characterized in that The secondary acid washing is followed by water washing to obtain a second silicon nanowire slurry.
28. The purification method according to claim 27, characterized in that The pH of the second silicon nanowire slurry is 6-8.
29. The purification method according to claim 27, characterized in that: The purification method further comprises ultrasonic dispersion.
30. The purification method according to claim 29, characterized in that The ultrasonic dispersion process comprises: After adding a dispersant to the second silicon nanowire slurry, ultrasonic dispersion and filtration are performed in sequence to obtain a second silicon nanowire material.
31. The purification method according to claim 30, characterized in that Based on the mass fraction of the silicon nanowire material to be purified being 100wt%, the amount of the dispersant added during the ultrasonic dispersion process is 0.1-0.5wt%.
32. The purification method according to claim 30, characterized in that The ultrasonic dispersion time is 1 to 60 minutes.
33. The purification method according to claim 30, characterized in that: The frequency of the ultrasonic dispersion is 40 to 60 kHz.
34. The purification method according to claim 30, characterized in that: The second silicon nanowire material is dried to obtain the purified silicon nanowire material.
35. The purification method according to claim 34, characterized in that The temperature of the drying treatment is 60-110°C.
36. The purification method according to claim 34, characterized in that The drying time is 5 to 30 hours.
37. The purification method according to claim 1, characterized in that The purification method comprises: (1) placing the silicon nanowire material to be purified in a primary acid solution for a primary acid wash for 1 to 5 hours, wherein the mass ratio of the primary acid solution to the silicon nanowire material to be purified is (17 to 27):1, and then washing with water to obtain a first silicon nanowire slurry with a pH of 6 to 8; (2) placing the first silicon nanowire slurry obtained in step (1) in a stirrer with a rotation speed of 15 to 80 rpm and a dispersion head speed of 500 to 3000 rpm for a primary dispersion of 3 to 90 min to obtain a silicon nanowire suspension; (3) placing the silicon nanowire suspension obtained in step (2) in a reaction kettle, adding a dispersant, and performing secondary dispersion for 3 to 90 minutes at a stirring rate of 10 to 200 rpm, wherein the amount of the dispersant added is 0.1 to 0.5 wt % based on the mass fraction of the silicon nanowire material to be purified as 100 wt %, and then filtering the suspension to obtain a first silicon nanowire material; (4) placing the first silicon nanowire material obtained in step (3) in a secondary acid solution with a concentration of 5 to 40 wt% for secondary acid washing for 1 to 5 h, wherein the mass ratio of the secondary acid solution to the first silicon nanowire material is (10 to 20):1, and then washing with water to obtain a second silicon nanowire slurry with a pH of 6 to 8; (5) After adding a dispersant to the second silicon nanowire slurry obtained in step (4), ultrasonic dispersion is performed at a frequency of 40 to 60 kHz for 1 to 60 minutes, and the amount of the dispersant added is 0.1 to 0.5 wt% based on the mass fraction of the silicon nanowire material to be purified as 100 wt%. After filtering, the second silicon nanowire material is obtained, and then the second silicon nanowire material is dried at a temperature of 60 to 110° C. for 5 to 30 hours to obtain a purified silicon nanowire material.
38. A silicon nanowire material, characterized in that: The silicon nanowire material is obtained by the purification method described in any one of claims 1-37.
39. A use of the silicon nanowire material according to claim 38, characterized in that: The silicon nanowire material is used as a negative electrode material for lithium-ion batteries.
Citation Information
Patent Citations
Recovery, purification and classification method of high-purity silicon carbide micro-powder
CN101804983A
Preparation method of beta-silicon nitride nanowire
CN101830447A
Preparation method of high-purity alpha-phase silicon nitride nanowire
CN112607715A